Pengaruh Fitur Layanan Dan Perception of Easy Terhadap Kepuasan Nasabah Pengguna Aplikasi BSI Mobile Pada Civitas Akademika UNHASY - Eka Meirita Indriani Saputri; Peni Haryanti (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
BSI Mobile application is BSI's effort to realize the expectations of its user customers. Service features and perception of ease are taken into account to increase customer satisfaction of BSI Mobile users. This study aims to determine the partial and simultaneous effects of service features and perception of easy on customer satisfaction. Simultaneous factors of service features and perception of easy on customer satisfaction users of BSI Mobile.This research using a causal associative approach. The population in this study is the UNHASY academic community, especially lecturers and employees. lecturers and employees. The sampling method is probability sampling technique and the sampling uses the Slovin formula with a total of 67 respondents. Furthermore, the respondent's data was analysed with data analysis techniques, namely validity test, reliability test, classical assumption test, and hypothesis testing. assumption test, and hypothesis testing. While in the discussion will review the views of Muslim economists regarding the research results.The results showed that partially and simultaneously variables of service features and perception of easy have a positive and significant effect on customer satisfaction of BSI Mobile users. significant on customer satisfaction of BSI Mobile users in the UNHASY academic community in 2024.